Clues to Fostering a Program Culture of Academic Integrity: Findings from a Multidimensional Model - Packalen, Kelley; Rowbotham, Kate (Canadian Perspectives on Academic Integrity, 2021)
Drawing on the responses from a survey of 852 undergraduates in a business program in Canada we identified situational, personality and contextual variables correlated with business students’ self-reported rates of academic integrity violations. The most influential predictors of increasing rates were: greater estimates of peers’ violations, increasingly negative perceptions of the program’s academic integrity culture, and rating questionable academic behaviours less seriously. Individual priorities, personal characteristics and social support were less influential. We then analyzed our quantitative results in light of our deep understanding of the broader context in which the students were located to derive richer insights from the interplay of our independent variables. Importantly, our results indicated that program-led proactive messaging designed to foster a culture of academic integrity could effectively buffer tendencies towards academic dishonesty. Absent ongoing messaging, however, increasing academic pressures may have eroded those initial benefits. Moreover, we identified how repercussions of major academic integrity breaches could be long lasting suggesting an even greater need for fostering academic integrity culture a priori. Based on our results we recommended a public health practice of identifying positive deviants – individuals who thrive in hostile environments – and then, in an effort to change a peer support system that fostered increasing rates of violations into one that does the opposite, engaging with those individuals to understand why and how they resisted the status quo.